Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the solutions to the equation [tex]\(9x^2 - 54x = 0\)[/tex], let's go through a step-by-step process.
### Step 1: Identify the given quadratic equation
The given equation is:
[tex]\[ 9x^2 - 54x = 0 \][/tex]
### Step 2: Factor out the common term
First, we factor out the greatest common factor (GCF) from both terms. The GCF in this case is [tex]\(9x\)[/tex]. Therefore, we can factor the equation as:
[tex]\[ 9x(x - 6) = 0 \][/tex]
### Step 3: Apply the Zero-Product Property
The zero-product property states that if the product of two factors is zero, then at least one of the factors must be zero. Therefore, we set each factor equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ 9x = 0 \quad \text{or} \quad (x - 6) = 0 \][/tex]
### Step 4: Solve each equation separately
1. Solve [tex]\(9x = 0\)[/tex]:
[tex]\[ x = 0 \][/tex]
2. Solve [tex]\(x - 6 = 0\)[/tex]:
[tex]\[ x = 6 \][/tex]
### Step 5: List all possible solutions
The solutions to the equation [tex]\(9x^2 - 54x = 0\)[/tex] are:
[tex]\[ x = 0 \, \text{and} \, x = 6 \][/tex]
### Step 6: Match the solutions with the given options
From the given answer choices:
- A. [tex]\(x = 7\)[/tex]
- B. [tex]\(x = 6\)[/tex]
- C. [tex]\(x = 0\)[/tex]
- D. [tex]\(x = -7\)[/tex]
- E. [tex]\(x = -6\)[/tex]
We can see that the correct answers are:
- B. [tex]\(x = 6\)[/tex]
- C. [tex]\(x = 0\)[/tex]
Therefore, the solutions to the equation [tex]\(9x^2 - 54x = 0\)[/tex] are [tex]\(x = 6\)[/tex] and [tex]\(x = 0\)[/tex].
### Step 1: Identify the given quadratic equation
The given equation is:
[tex]\[ 9x^2 - 54x = 0 \][/tex]
### Step 2: Factor out the common term
First, we factor out the greatest common factor (GCF) from both terms. The GCF in this case is [tex]\(9x\)[/tex]. Therefore, we can factor the equation as:
[tex]\[ 9x(x - 6) = 0 \][/tex]
### Step 3: Apply the Zero-Product Property
The zero-product property states that if the product of two factors is zero, then at least one of the factors must be zero. Therefore, we set each factor equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ 9x = 0 \quad \text{or} \quad (x - 6) = 0 \][/tex]
### Step 4: Solve each equation separately
1. Solve [tex]\(9x = 0\)[/tex]:
[tex]\[ x = 0 \][/tex]
2. Solve [tex]\(x - 6 = 0\)[/tex]:
[tex]\[ x = 6 \][/tex]
### Step 5: List all possible solutions
The solutions to the equation [tex]\(9x^2 - 54x = 0\)[/tex] are:
[tex]\[ x = 0 \, \text{and} \, x = 6 \][/tex]
### Step 6: Match the solutions with the given options
From the given answer choices:
- A. [tex]\(x = 7\)[/tex]
- B. [tex]\(x = 6\)[/tex]
- C. [tex]\(x = 0\)[/tex]
- D. [tex]\(x = -7\)[/tex]
- E. [tex]\(x = -6\)[/tex]
We can see that the correct answers are:
- B. [tex]\(x = 6\)[/tex]
- C. [tex]\(x = 0\)[/tex]
Therefore, the solutions to the equation [tex]\(9x^2 - 54x = 0\)[/tex] are [tex]\(x = 6\)[/tex] and [tex]\(x = 0\)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.